Patient satisfaction with pharmacy services among users and non users of community based health insurance scheme at public health facilities in Gamo Zone, South Ethiopia: a comparative cross sectional study - Fitsum Teferi Gulta; Tidenek Mulugeta; Biruk Wogayehu; Mende Mensa (BMC, 2024)
Abstract Background Patient satisfaction is a crucial humanistic outcome metric in pharmacy services. There was a lack of evidence on patients' satisfaction with pharmacy services in Gamo zone among users and nonusers of the CBHI scheme. Therefore, the aim this study is to compare the level of patient satisfaction with pharmacy services among users and nonusers of community based health insurance scheme at public health facilities in Gamo zone, South Ethiopia. Method A facility based comparative cross sectional study design with mixed approach was conducted from June 1 to 30, 2023. A total of 522 study participants and 16 key informants were included as the sample size for quantitative and qualitative study, respectively. The quantitative data was gathered from the study participants who visited the outpatient pharmacy department during the study period by using a simple random sampling technique, while the purposive sampling technique was used to select clients and key informants for the qualitative study. The adjusted odds ratio (AOR) was used to measure the association between independent variables and patient satisfaction toward outpatient pharmacy services at the P values < 0.05 and 95% confidence interval (CI). Results From the total of study participants, 195 (73.9%) of insured and 175 (67.8%) of noninsured clients were satisfied with pharmacy services offered at public health facilities. The gender of insured (95% CI = 2.00-12.36, (p 0.01)), and noninsured (95% CI = 0.658-2.881, (p 0.02)), waiting time of insured (95% CI = 0.057-0.766, (p 0.0027)), and noninsured (95% CI = 0.084-0.925, (p 0. 0021)) and premium affordability of insured (95% CI = 0.0605-4.860, (p 0.00)) were significantly associated factors with client satisfaction at p < 0.05 and 95% CI. Based on qualitative finding, as member of the CBHI scheme, the members had a greater opportunity to receive a good pharmacy services, because they were more familiar with the physicians and the institutions. Conclusion The clients with insurance perceived high level of satisfaction with pharmacy services in public health facilities than noninsured. The gender and waiting times at outpatient pharmacy department for both groups of study participants and the premium affordability for the insured groups of clients were factors affecting client satisfactions with pharmacy services.